The Role of Energy Security In Supporting Indonesia's National Security: A Strategic Approach - Maulia Ikhsan Sopali (Jurnal Indonesia Sosial Sains, 2025)
This research aims to develop and implement an energy security index in Indonesia and analyze problems related to energy security. This research uses a qualitative approach with a case study method, which was carried out in several locations such as the Ministry of Energy and Mineral Resources (EMR), the Downstream Oil and Gas Regulatory Agency (BPH Migas), and national energy companies such as PT Pertamina and PT PLN. The subjects of the study include government officials, energy company executives, and energy experts who play a role in energy policy and management. Data were collected through in-depth interviews, participatory observations, and document analysis. Key indicators used to compile the energy security index include the availability of energy supply, dependence on energy imports, diversification of energy sources, and energy efficiency. Thematic analysis and content analysis are used to analyze the data that has been collected. The interim statement suggests that the energy security index can identify key problems in Indonesia's energy sector, including a high dependence on energy imports and a lack of diversification of energy sources. The study also found that strategies to improve energy security, such as the development of renewable energy and improved energy efficiency, can contribute significantly to national security. The conclusion of this study emphasizes the importance of a multidisciplinary approach and international cooperation in addressing energy security challenges.